Effectiveness of Self-Help Books for Improving Santris' Mental Health Literacy - Ahmad Rofi Suryahadikusumah; Imam Nur Alam; Desi Triana; Yuli Nurmalasari (State Islamic University (UIN) Salatiga, 2024)
Mental health literacy is needed so that Santris better understands the dynamics within themselves and knows the risk factors that can disrupt their mental health. The growth of Santri's psycho-social problems such as bullying, theft, and running away from the dormitory is not far from mental health literacy, especially in managing mood. The obstacles experienced by Islamic boarding schools are the density of education programs and the need for more human resources, such as guidance and counseling teachers in Islamic boarding schools. Therefore, researchers offer a solution through developing a self-help book. The research aims to test self-help books to increase mental health literacy. The method used was quasi-experimental with a sample of 58 santris at the Peradaban Islamic Boarding School. Sample selection was carried out using purposive sampling. Mental health literacy was measured using a Mental Health Literacy Questionnaire (MHLQ). The Self-Help book has been proven effective for developing Santris' mental health literacy, based on differences in mental health literacy scores before (x̄ =114) and after(x̄ =119) Santris read and follow guided exercises in self-help books (p = .000, p < .05). The change in the mental health literacy dimension that has increased the most is the resource dimension (ability to manage self and maintain mental health). The experience of reading and following the guidelines in self-help books makes Santris more capable of managing themselves, as well as having basic skills in coping strategies.